2017
DOI: 10.1111/1759-3441.12195
|View full text |Cite
|
Sign up to set email alerts
|

Money, Lending and Banking Crises

Abstract: This paper shows that the bank lending channel impacts on lending and on the risk of a banking crisis. The results show that an increase in interest rates will decrease future bank lending and the likelihood of a banking crisis. This effect is dampened during recessionary periods in European countries. Policy implications are also provided. The detrimental effects of a lax monetary policy on a crisis are reduced directly by a highly capitalised financial sector and indirectly in an economy with highly liquid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Failure to maintain effective credit standards with increasing loan portfolios may raise the possibility of bad loans (Ekanayake and Azeez 2015;Klein 2013). Keeton (1999), Khemraj and Pasha (2009), Meela and Prasad (2016), and Sinkey and Greenawalt (1991) showed that rapid credit growth is usually associated with poor lending decisions, indicating the probability of bad loans and the likelihood of a banking crisis increase with the increase in the LAR (Peña 2017). In contrast, Shingjergji (2013) found a negative effect of LAR on NPLs in the Albanian banking industry, which suggest an increase in the loan portfolio may not increase the NPL level.…”
Section: Effects Of Banking Management On Non-performing Assets (Npas)mentioning
confidence: 99%
“…Failure to maintain effective credit standards with increasing loan portfolios may raise the possibility of bad loans (Ekanayake and Azeez 2015;Klein 2013). Keeton (1999), Khemraj and Pasha (2009), Meela and Prasad (2016), and Sinkey and Greenawalt (1991) showed that rapid credit growth is usually associated with poor lending decisions, indicating the probability of bad loans and the likelihood of a banking crisis increase with the increase in the LAR (Peña 2017). In contrast, Shingjergji (2013) found a negative effect of LAR on NPLs in the Albanian banking industry, which suggest an increase in the loan portfolio may not increase the NPL level.…”
Section: Effects Of Banking Management On Non-performing Assets (Npas)mentioning
confidence: 99%
“…Lee and Lim (2019) revealed that larger service sectors also tend to increase the risk of the banking crisis. Peña (2017) facilitated that increasing interest rates will decrease future bank lending and accelerate the likelihood of a banking crisis. Vouldis and Louzis (2018) asserted that decline in industrial production is also a good predictor of financial crises.…”
Section: Literature Reviewmentioning
confidence: 99%